2019
DOI: 10.1002/er.4980
|View full text |Cite
|
Sign up to set email alerts
|

Thermoacoustic combustion instability of propane‐oxy‐combustion with CO2dilution: Experimental analysis

Abstract: In this study, the effect of CO 2 dilution on the thermoacoustic stability of propane-oxyfuel flames is studied in a non-premixed, swirl-stabilized combustor. The results, obtained at a fixed combustor power density (4 MW/m 3 bar)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
(121 reference statements)
0
11
0
Order By: Relevance
“…Temperature and species fractions, that is, densityweighted average scalars, can be evaluated from the probability density function (PDF) and progress variable using Equation (24). Subscripts, u and b, in this expression correspond to unburnt and burnt mixtures, respectively.…”
Section: Numerical Modeling 221 | Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and species fractions, that is, densityweighted average scalars, can be evaluated from the probability density function (PDF) and progress variable using Equation (24). Subscripts, u and b, in this expression correspond to unburnt and burnt mixtures, respectively.…”
Section: Numerical Modeling 221 | Governing Equationsmentioning
confidence: 99%
“…Among these, swirl-stabilized burners have been investigated the most for oxycombustion application. [13][14][15][16][17][18] Moreover, oxy-combustion of various fuels (eg, methane, [19][20][21] propane, [22][23][24] syngas, [25][26][27] ammonia, [28][29][30] and hydrogen [31][32][33] ) at varying combustion parameters, such as equivalence ratio (ϕ), oxygen fraction (OF), adiabatic flame temperature (T ad ), and flame speed (FS), has been examined as well. Most research is focused on methane, with fewer studies examining propane.…”
Section: Introductionmentioning
confidence: 99%
“…Lean premixed combustion techniques are extensively employed in the power generation or aviation gas turbine combustors 1,2 . Due to the decreased equivalence ratio and the local flame temperature, the NO x formation would reduce exponentially in the lean premixed combustor.…”
Section: Introductionmentioning
confidence: 99%
“…Combustion instability is among the most critical operational challenges encountered in combustion systems of gas turbines, rockets, industrial boilers, furnaces and so on. Thermoacoustic instability can be formed with the coupling of sound pressure and heat release fluctuations in the combustion chamber 2 . These acoustic fluctuations may reach sufficient amplitude to interfere with gas turbine operation and, in extreme cases, lead to failure of the system due to excessive structural vibration and heat transfer to the chamber 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The rise in the local flame temperature results in faster expansion of the reaction zone, inhibiting the cooler flow recirculation 11 . Effects of hydrogen enrichment on the flame shape and thermoacoustic oscillation dynamics of methane blends in lean premixed gas turbine combustion was studied by Karlis et al 25 It was found that increasing the H 2 content keeping other operational parameters constant, increases the extinction strain rate leading to dynamic state transition. Moreover, studies by Abubakar and Mokheimer 25 on the thermoacoustic instability of propane oxy‐combustion shows that the increase of hydrogen fraction in the fuel blend lowers the acoustic amplitude.…”
Section: Introductionmentioning
confidence: 99%